Glosa do biografii Herminy von Reuss = A gloss on the biography of Hermina von Reuss - Chmielewski, Grzegorz (Zielona Góra: "Pro Libris" Wydawnictwo Wojewódzkiej i Miejskiej Biblioteki Publicznej w Zielonej Górze)
The text describes the life of Hermine von Reuss, the wife of former German emperor Wilhelm II, during the years of World War II. It presents her visits to German spa towns, her correspondence with local authorities, and her life after her husband's death in 1941. An analysis of her letters, books from her library, and her actions toward people around her suggests that she showed sympathy for Nazi ideology and expressed a positive attitude toward Hitler?s leadership. At the same time, some researchers emphasize that certain statements may have been opportunistic or patriotic rather than purely ideological.After Wilhelm II?s death, Hermine returned to Zabór, where she maintained relations with estate workers and gave gifts to their children, including books with Nazi content. In the final phase of the war, she left the palace while fleeing the approaching Red Army. Eventually, she ended up in the Soviet occupation zone, was questioned by Soviet authorities, and died in 1947 in Frankfurt (Oder).
Keywords: Hermine von Reuss-Hohenzollern (1887-1947); Wilhelm II; Adolf Hitler; Bad Kissingen; Frankfurt nad Odrą; Zabór; Armia Czerwona; II wojna światowa (1939-1945); nazizm; propaganda; Gestapo; ewakuacja; Rzesza Niemiecka; Red Army; world war II; nazism; evacuation; censorship; Reich